REVITALISASI POSYANDU DAN PELATIHAN KADER TENTANG PELAKSANAAN KEGIATAN POSYANDU SISTEM 5 MEJA - Tri Tunggal; Erni Setiawati; Arie Heryanti (Jurnal Bakti untuk Negeri, 2021)
Community service is the third dharma of the Tridharma of Higher Education. The community service carried out is "Training Posyandu Cadres on 5-table System Services (Community-Based Health Efforts) in the Work Area of the Matraman Health Center, Banjar Regency. The target group is cadres in Posyandu in 4 (four) villages, namely Simpang Tiga Village, Pasiraman Village, Bawahan Pasar Village and Bawahan Selan Village in the Working Area of the Matraman Health Center. Posyandu, in addition to functioning as a forum forcommunity empowerment in the transfer of information and skills from officers to the community and between fellow citizens, also to bring basic health services closer, especially with regard to MMR, IMR, and AKBA. throughout Indonesia.The purpose of this community service is so that every Posyandu cadre has theability to implement the 5 Table Service System.